Caregivers' knowledge of autism in a local peri-urban community of Nepal: A cross-sectional study in Kirtipur, Kathmandu. (February 2021) - Shrestha, Rena; Dissanayake, Cheryl; Barbaro, Josephine
Highlights: Findings showed a substantial lack of knowledge about autism among Nepalese caregivers. Caregivers over 25 years, with more than secondary education and belonging to the upper caste, had more knowledge of autism. Urgent need for awareness programmes to raise caregivers' understanding about autism. Abstract: Early markers of autism emerge during the first two years of life with a reliable diagnosis possible by 24 months of age. Caregivers' knowledge about autism is crucial to facilitate the early identification of autism. However, research on caregivers' knowledge of autism in low- and middle-income countries (LMICs) is scarce. The current study examined Nepalese caregivers' knowledge about autism and potential differences in knowledge as a consequence of demographic characteristics. A population-based cross-sectional survey was conducted with 1895 caregivers (Mean age = 28 years, SD = 5.2) with children between 11–30 months of age in Kirtipur Municipality in Kathmandu, Nepal. Although Nepalese caregivers showed strong knowledge on early social attention and communication behaviours in infants/toddlers, only one-fourth reported any knowledge about autism. Moreover, knowledge on autism differed significantly by caregivers' age, education and caste/ethnicity. Caregivers over 25 years of age, with more than secondary education and belonging to the upper caste and advantaged groups, had more knowledge about autism. The significant lack of knowledge regarding autism amongst Nepalese caregivers indicates the need to raise awareness, targeting caregivers from all ages, educational levels and caste/ethnic groups, to facilitate early recognition of autism.